Analisis Implementasi Kebijakan Relaksasi Pembiayaan Nasabah Umkm Pada Unit Pelaksana Teknis Daerah Fasilitasi Pembiayaan Kota Payakumbuh Pada Masa Pandemi Covid-19 - Hamidah (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The outbreak of the COVID-19 pandemic that emerged in Indonesia caused various changes in the order of social life. This phenomenon has a very bad impact on the economic sector, especially MSMEs. As a result of the quite severe impact felt by MSMEs is the difficulty in making payments or through credit/credit. This study discusses how to implement a relaxation policy for MSME customer financing at the UPTD of Financing Facilities during the covid-19 pandemic. The approach applied in this research is a qualitative approach using George III Edward's policy theory. Data was collected by means of interviews, Focus Group Discussions (FGD) and document studies. The results of the study: The implementation of the MSME financing relaxation policy in UPTD-FP which has not run as expected. Although the implementation is in accordance with the existing policies, in its implementation there are unsatisfactory achievements. Although internal communication between policy makers and policy implementers is good enough, communication to customers is considered not optimal. The socialization program to customers is uneven, resulting in not all customers getting information about the relaxation program. results, not many customers benefit from the program. Keywords : Covis-19 Pandemic, MSMEs, Credit relaxation, Implementation